(untitled) (International Journal of Current Engineering and Technology, 2015)
This paper focuses on comparison on formal specification languages and chooses the appropriate one for a particular problem. Formal specification is a better way to identifying specification errors and describing specification in unambiguous ways. Formal specification is a specification written in a formal language where a formal language is either based on rigorous mathematical model or simply on standardized programming or specification language. Formal specification language expressed the specification in a language whose vocabulary syntax and semantic are properly defined. Formal specification language provides mathematical representation of the system. In this paper I will introduce three formal specification languages such as Z, VDM, and B and perform comparison among to them.